Evaluating the Environmental Impact: A Multisensor Remote Sensing Approach for Spatial and Temporal Analysis - Bin Zhu; Ahsen Maqsoom; Lapyote Prasittisopin; Chaudhary Danyal Aslam; Umer Khalil; Sahar Zia; Niamat Ullah; M. Abdullah-Al-Wadud; Nazih Yacer Rebouh (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
This study quantifies the potential environmental impacts of the Karakoram highway (KKH) construction, which links the northern region of Pakistan with Western China. The upgrade of the KKH was carried out under the China-Pakistan Economic Corridor (CPEC) project. We examined highway construction's spatial and temporal effects on the immediate environment and the ecological revival progressions through remotely sensed images taken at distinct points in time. Here, using a buffer zone of 20 km along the KKH (10 km on both sides), we estimated the before-during-after remote sensing-based factors that relate to the ecology to compute the geographical and temporal variations of environmental effects during the building of the KKH. The outcomes showed that whereas land cover makeup remained broadly consistent in the south of the buffer, it underwent significant changes in the upper portion as we moved more and more towards the north. The buffer region showed clear degradation-recovery trends in the moistness and vegetation states, as evidenced by the normalized difference moisture index (NDMI) and the normalized difference vegetation index (NDVI) correspondingly. Meanwhile, the land surface temperature (LST) gradually increased. The maximum relative changes in NDMI, NDVI, and LST were roughly 60%, 40%, and 12%, respectively. According to an Integrated environment quality index, the effects of highway developments on the environment were most pronounced in the immediate vicinity and diminished with distance. This study's method for quantifying highway system disturbances' spatial and temporal changes and subsequent recovery can be easily extended to different geographical areas.